Individual and collective behavior in confronting Covid-19 in a small town: an experience report (Research, Society and Development, 2021)
The Covid-19 pandemic has strongly affected Brazil since 2020, especially as small cities due to the lack of infrastructure to meet the needs of the population affected by the disease. The work consists of an experience report on a Project, promoted by the Federal University of Delta do Parnaíba, raising action strategies to combat the new coronavirus in the small town, neighboring the institution. Providing information to places where access to them is scarcer, in addition, given the condition of social vulnerability found in some parts of the city, cloth masks, soap and soap were collected and distributed for prevention and awareness of the most humble. Thus, it was possible to analyze the scenario in the fight against the virus, portray the main facts and how the social condition and lack of information can negatively impact this control.